Human autonomy in cross-cultural context perspectives on the psychology of agency, freedom, and well-being - Chirkov, Valery I.; Ryan, Richard M; Sheldon, Kennon M; SpringerLink (Online service). (New York Springer, 2011)
Collection of multi-disciplinary essays explores the nature of personal autonomy, considering its developmental origins, its expression within relationships, its importance within groups and organizational functioning, and its role in promoting the democratic and economic development of societies. In Human Autonomy in Cross-Cultural Context: Perspectives on the Psychology of Agency, Freedom, and Well-Being, the starting point for all essays is self-determination theory, which is an integrated theory of human motivation and healthy development that has been under development for more than three decades. From there, the essays go on to provide the following: a theoretical and conceptual account of the nature and psychological mechanisms of personal motivational autonomy and human agency; rich, multidisciplinary empirical evidence supporting the claims and propositions about the nature of human autonomy and capacities for self-regulation; explanations of how and why different psychological and socio-cultural conditions may play a role in promoting or undermining people's autonomous motivation and well-being; and discussions of how the promotion of human autonomy can positively influence environmental protection, democracy promotion and economic prosperity. While the topics in this text are varied, the authors all share a vision that human autonomy is a fundamental pre-condition for both individuals and groups to thrive. They also collectively believe that without understanding the nature and mechanisms of autonomous agency, vital social and human problems cannot be satisfactorily addressed
Introduction. The Struggle for Autonomy in Personal and Cultural contexts: An Overview, Valery I. Chirkov, Kennon M. Sheldon, and Richard M. Ryan -- Part 1. A Theoretical Context of Human Autonomy, People?s Well-Being, and Happiness -- 1. Positive Psychology and Self-Determination Theory: A Natural Interface, Kennon M. Sheldon and Richard M. Ryan -- 2. A Self-Determination Theory Perspective on Social, Institutional, Cultural, and Economic Supports for Autonomy and their Importance for Well-being, Richard M. Ryan and Edward L. Deci -- 3. Dialectical Relationships among Human Autonomy, the Brain, and Culture, Valery I. Chirkov -- Part II. Human autonomy across cultures and domains of life: health, education, interpersonal relationships, and work -- 4. The Role of Autonomy in Promoting Healthy Dyadic, Familial, and Parenting Relationships across Cultures -- C. Raymond Knee and Ahmet Uysal -- 5. Do Social Institutions Necessarily Suppress Individuals? Need for Autonomy? The Possibility of Schools as Autonomy Promoting Contexts across the Globe, Johnmarshall Reeve and Avi Assor -- 6. Well-being, Physical Health, and Personal Autonomy, Geoffrey Williams, Pedro J. Teixeira, Eliana Carraca, and Ken Resnicow -- 7. Autonomy in the Workplace: An Essential Ingredient to Employee Engagement and Well-Being in Every Culture, Marylène Gagné and Devasheesh Bhave -- Part III. Human autonomy in modern economy, democracy development, and sustainability -- 8. Capitalism and Autonomy, Tim Kasser -- 9. Economy, People?s Personal Autonomy, and Well-Being, Maurizio Pugno -- 10. The Development of Conceptions of Personal Autonomy, Rights and Democracy and their Relation to Psychological Well-Being, Charles C. Helwig and Justin McNeil -- 11. Personal Autonomy and Environmental Sustainability, Luc G. Pelletier, Daniel Baxter, and Veronika Huta
Keywords: Autonomy (Psychology).; Autonomy; Psychology; Electronic books